2007
DOI: 10.1556/avet.55.2007.4.7
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a combination of formic and propionic acids added to wheat- and barley-based diets on the performance and gut histomorphology of broiler chickens

Abstract: Day-old male chicks were used to test the effects of a combination of formic and propionic acids (CFP) added to wheat-and barley-based diets on the performance and gut histomorphology of broilers. The CFP, containing formic and propionic acids based on an inorganic phyllo-silicate carrier, was added to starter and grower broiler diets of standard (NRC, 1994) or lower nutrient density (LND) using different levels of wheat and barley. Body weight gain (BWG) and feed conversion ratio (FCR) of broiler chicks were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
19
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 20 publications
6
19
0
4
Order By: Relevance
“…These results are in harmony with the other workers [9,26,8,14] who reported that supplementation of organic acids in broiler chicken improved the body weight gain in broiler chicken. In the present study, the effect of dietary organic acids on body weight gain was highly significant (p<0.05) from 3 to 6 weeks of age confirming earlier results of Senkoylu et al [20]. The improvement in body weight gain might be due to direct antimicrobial effect of organic acids as reported by Ricke [18] that organic acids may affect the integrity of microbial cell membrane or cell macromolecules or interfere with nutrient transport and energy metabolism causing bactericidal effect.…”
Section: Resultssupporting
confidence: 91%
“…These results are in harmony with the other workers [9,26,8,14] who reported that supplementation of organic acids in broiler chicken improved the body weight gain in broiler chicken. In the present study, the effect of dietary organic acids on body weight gain was highly significant (p<0.05) from 3 to 6 weeks of age confirming earlier results of Senkoylu et al [20]. The improvement in body weight gain might be due to direct antimicrobial effect of organic acids as reported by Ricke [18] that organic acids may affect the integrity of microbial cell membrane or cell macromolecules or interfere with nutrient transport and energy metabolism causing bactericidal effect.…”
Section: Resultssupporting
confidence: 91%
“…In our study, the addition of MCFA, and the simultaneous addition SCFA + MCFA or SCFA + inulin had a beneficial effect on the selected biomechanical indicators of the tibia bones. This influence can be probably attributed to improved availability of Ca and P by virtue of a decrease in pH in the upper part of the intestine and the stimulating effect of organic acids on villus height, which was observed in broilers by Senkoylu et al (2007). It has also been proposed that organic acids (citric acid) improved Ca availability by chelating Ca and reducing the formation of insoluble Ca-phytate-complexes (Boling et al 2000).…”
Section: Resultsmentioning
confidence: 98%
“…Sacakli et al (2006) indicated that the addition of short chain organic acids (lactic + formic acid) to the diet for quail improved utilization of dietary phosphorus and increased the content of crude ash in tibia bones. Inulin or organic acids added to the diet for broilers increased the length of intestinal villus (Rehman et al 2007;Senkoylu et al 2007), which might stimulate the absorption of minerals. The aim of the experiment was to study the effect on the biomechanical and geometrical properties of tibia and femur bones when short (SCFA), or medium chain fatty acids (MCFA), or prebiotic fructans with different lengths of chain (inulin or oligofructose) are added to the layer's diet at different levels of Ca and P.…”
mentioning
confidence: 99%
“…That is in agreement with , but opposite to the findings of pelicano et al (2005) and Samanta et al (2010) who reported higher villi in the ileum as well, following supplementation of an orthophosphoric, formic, propionic acid and calcium propionate blend. Senkoylu et al (2007) made similar observations trying a combination of formic and propionic acid. The increased villus height and decreased width contributed to more extended surface area available for nutrient absorption, although the crypt depth was found decreased.…”
Section: Organic Acids Against Important Poultry Pathogensmentioning
confidence: 56%
“…contaminated feed (Dixon and Hamilton, 1981;Thompson and Hinton, 1997). The dietary acidification was found to resemble the effect of AGps in the gastrointestinal tract of farm animals (Senkoylu et al, 2007), so, many studies, especially on swine, have focused on examining the effect and mode of action of organic acids added in the feed. In poultry production, organic acids have not gained as much attention as in swine production, because there is lack of consistency in the results and great variability in the performance (Dibner and Buttin, 2002).…”
Section: Introductionmentioning
confidence: 99%